23 PERICARDIUM: RISK FACTOR FOR POST-PERICARDIOTOMY SYNDROME?. (1st March 2005) - Lam, C.; Cha, J. Y.; Altaye, M.; Manning, P.; Eghtesady, P.
Abstract : Background: In congenital heart surgery post-pericardiotomy syndrome (PPS) is most often noted after repair of simple ASD (atrial septal defect). The etiology of PPS remains unknown. PPS often presents as a significant pericardial effusion after ASD repair. We hypothesize after heart surgery PPS is caused by an immunologic reaction against the pericardium, due to exposure of this normally immunologically privileged tissue to the blood stream. Moreover, we hypothesize glutaraldehyde-treated (GLUT) pericardial patch would further increase the antigenicity, leading to a greater immunologic reaction. Methods: A retrospective review of patients that had undergone ASD repair from 1996 to 2003 was performed. Preoperative and postoperative echocardiograms were reviewed for ASD size, degree of RV enlargement, and size of pericardial effusions. In addition clinical symptoms of PPS were noted. Operative reports were reviewed for type of ASD repair technique. Three repair techniques, primary closure, GLUT patch closure, and non-GLUT patch closure, were compared using a generalized linear model with Poisson link function while controlling for potential confounders. Results: Among the 186 patients, 44.1% (82/186) underwent primary closure while 55.9% (104/186) underwent patch closure. Among the patch closure patients 67.3% (70/104) were repaired with a GLUT-patch, while 32.7% (34/104) were repaired with a non-GLUT patch. Age, sex, ASD size, and degree of RV enlargement were not significant variables on multivariate analysis. The incidence of pericardial effusion varied between groups: 2.4% (2/82) in primary, 2.9% (1/34) in non-GLUT patch, and 12.9% (9/70) in GLUT patch. The relative risk of developing pericardial effusion with a GLUT patch when compared to non-GLUT patch and primary was 4.4 (CI -0.5, 34.5) and 5.3 (CI 2.2, 24.4), respectively. Finally, the incidence of moderate to large effusions also varied significantly between groups: GLUT patch group 8.6% (6/70) versus non-GLUT patch group 0.0 % (0/34), p = 0.03, and primary 0.0% (0/82), p = 0.007. Conclusions: The use of pericardial patch in repair of ASD substantially increases the risk of PPS. The risk is further exacerbated with GLUT treatment of the pericardium. An autoimmune reaction against novel antigens created by GLUT cross-linking of pericardial proteins may be involved. Further studies are warranted to explore potential immunologic mechanisms involved.